Identification of the human salivary cystatin complex by the coupling of high-performance liquid chromatography and ion-trap mass spectrometry - Lupi, Alessandro; Messana, Irene; Denotti, Gloria; Schininà, Maria Eugenia; Gambarini, Gianluca; Fadda, Maria Benedetta; Vitali, Alberto; Cabras, Tiziana; Piras, Vincenzo; Patamia, Maria; Cordaro, Massimo; Giardina, Bruno; et al. (Proteomics (Weinheim), 2003)
Human salivary cystatins, five major (S, S1, S2, SA, SN) and two minor (C and D), are multifunctional proteins playing a different role in the oral environment. Salivary cystatin SN is able to effectively inhibit lysosomal cathepsins B, C, H and L and cystatin SA inhibits cathepsins C and L in vitro. These activities suggest, particularly for cystatin SN, an important role in the control of proteolytic events in vivo. Differently, cystatins S are involved, together with statherin, in the mineral balance of the tooth. Due to their distinct role, a reliable method for identification and quantification of the different cystatins, as well as of possible truncated and derived forms, could be helpful for the assessment of the status of the oral cavity. To this purpose high‐performance liquid chromatography electrospray ionization mass spectrometry (HPLC‐ESI MS) was applied to the analysis of human saliva obtained from healthy subjects. All known salivary cystatins, with the exception of cystatin C, were detected. Strong evidence was also obtained for the presence in saliva of post‐translational modified isoforms of cystatins, which may be related to donor habits. Cystatin SN and cystatins S, S1 and S2 were well separated by HPLC‐ESI MS coupling from other components and thus this approach can be successfully applied to their quantification.